Plan estratégico para el desarrollo empresarial del centro de acopio Parraga, cantón Mocache, periodo 2014-2017 - Plua Solorzano, Susy Liliana (2015)
This study deals with the design of a strategic plan that begins with an analysis of the current situation and then propose strategic actions for the Collection Center Parraga, dedicated to the marketing of yellow corn. The collection center has about a highly trained staff to perform functions technologically advanced facilities. From the available information gathered from internal to the company, are analyzed in detail the four functional areas: administration, finance-accounting, production-service and marketing. The administration area is related to the operation of the company, was learned based on the analysis of results obtained in the research, strategies that result in improved processes and procedures. The financial and accounting analysis focuses on the study of basic accounting information of the company, although the financial statements are handled with some stealth. For the product or service can meet mercadológicos aspect such as suppliers, equipment, machinery and installed capacity owned by the company. In marketing area clearly analyzed the relationship of farmers, their behavior and satisfaction of their needs, design new marketing methods to achieve market positioning. Next, secondary information which laid the foundations for the study of the distribution center environment, with emphasis on overall economic aspects was compiled, without neglecting political, technological and social. The theme of the competition was analyzed by hand, given its importance to the company and the current situation was investigated. Which determine the opportunities and threats in the external environment presents the entity. It concludes with a proposed strategic plan, where hard in directionality Collection Center Parraga is made, its strategic policy decisions, objectives and strategic options. The strategic plan is a document adaptable to any company and given the fact that the gathering need for a guideline to improve your current administration. Chapter I: Introduction, problem, problem formulation, systematization of the problem, justification, Aim, specific objectives, assumptions are addressed. Chapter II: Based on the Theoretical Foundation, Conceptual Foundations and Legal Foundations based on the theme of research development. Chapter III: Materials and Research Methods, Types of Research, Design, techniques, sources, methods of data collection: Methodology is located. Chapter IV: Results and interpretation of surveys conducted among suppliers and employees Parraga Collection Center is located. Chapter V: Here are the conclusions and recommendations. Chapter VI: Development of presenting a strategic profile, draft strategic plan and action plan Strategic Plan is located. Chapter VII: Consists of literature. Chapter VIII: Annexes are available.